Management of Extensive Dermatophytosis: A Comprehensive Review - Harshitha, M.; Karunandhan, Manobalan; S, Srikanth. (Journal of Neonatal Surgery, 2025)
Dermatophytosis is a superficial fungal infection of the skin caused by keratinophilic fungi. Based on the extent of body surface area involved, it can be classified as mild, moderate and severe (extensive) infection. Topical antifungals can be used for treating mild to moderate infections whereas, for extensive involvement, systemic antifungal therapy is the mainstay of treatment. The most commonly used oral antifungals for treating dermatophytosis are fluconazole, terbinafine, itraconazole, griseofulvin, ketoconazole and rarely amphotericin-B, voriconazole and posaconazole. Presently, there is an adequate armamentarium of oral antifungal drugs but despite this, there is a rising trend of recalcitrant and recurrent dermatophyte infections. The reasons for this could be the emergence of resistance to the currently used antifungals, poor compliance of the patient to the treatment owing to the exorbitant cost of the newer oral antifungal drugs.